Pandemic preparedness in shaping psychosocial working conditions – insights for occupational safety and health from a longitudinal mixed-methods study during the COVID-19 pandemic at six company sites of one organization in Germany - Jana Soeder; Christine Preiser; Anke Wagner; Anna T. Neunhöffer; Falko Papenfuss; Juliane Schwille-Kiuntke; Andrea Wittich; Esther Rind; Monika A. Rieger (PLoS ONE, 2025)
Objectives This longitudinal mixed-methods study explores how one company group dealt with COVID-19 pandemic-related challenges and how employees and managers perceived work-related psychosocial demands in Germany. Materials and methods We analyzed panel survey data from 322 employees and managers across diverse working fields, e.g., assembly line/production, office, company medical service, and factory security service. Employees and managers were recruited from six German company sites in the federal states of Bavaria, Baden-Wurttemberg, and Lower Saxony of one large company group. The survey was conducted in August-October 2020, January 2021, and October-November 2021. Participants self-reported their perceived psychosocial demands from aspects of work organization, work environment, work content, and social relations at work during and retrospectively before the COVID-19 pandemic on a 5-point Likert scale. Additionally, nine managers were interviewed in September-October 2020 and April-May 2021 about pandemic-related changes in working conditions, organizational processes to adapt working conditions, and a culture of trust. For contextualization, we performed a comprehensive document analysis of prevailing national and federal laws and OSH-regulations for infection control in Germany. Results Quantitative results revealed that participants perceived stable psychosocial demands during the pandemic. Psychosocial demands relating to work organization were perceived as stressful, especially for managers and company's medical service personnel. No statistically significant changes were identified with respect to psychosocial demand ratings during compared to before the pandemic. Qualitative results highlighted that a crisis management team, a culture of trust, extensive and transparent communication, and participatory approaches in change processes were key to managing pandemic-related challenges. Conclusion Our findings contribute to a contextualized understanding of how the design of good and sustainable working conditions ensuredwork ability during the COVID-19 pandemic in Germany. They highlight the importance of pandemic preparedness in an organization's psychosocial work design to successfully manage challenging times. The derived learnings for organizational pandemic preparedness on a meso-, macro-, and micro-level are of lasting significance with a view to future global challenges in terms of the design of good psychosocial working conditions.